Book Review: Xavier Bougarel (2018). "Islam and Nationhood in Bosnia-Hercegovina: Surviving Empires". London-New York: Bloomsbury Academic - Maciej Falski (Colloquia Humanistica, 2019)
Book Review: Xavier Bougarel (2018). Islam and Nationhood in Bosnia-Hercegovina: Surviving Empires. London-New York: Bloomsbury Academic